Factors Related to Heat Strain in Tough-Making Industrial Workers - Adjie, Sahrul; Putri, Dian Utama Pratiwi; Djamil, Achmad (GLOBAL HEALTH SCIENCE GROUP, 2024)
Tofu manufacturing industry workers are a group that is vulnerable to heat strain due to exposure to high heat during work. Heat strains can cause serious health problems such as heat stroke, heat exhaustion, and heat cramps. Objective: This research aims to analyze factors related to heat strain in tofu making industry workers in South Kotabumi District, North Lampung Regency in 2024. Method: This study used a cross-sectional design. The population is all workers in the tofu making industry in South Kotabumi District, North Lampung Regency. Samples were taken using a total sampling technique, namely 30 workers. Data was collected through interviews, measurements and observations. Data analysis was carried out univariately, bivariately using the Chi-square test, and multivariately using the logistic regression test. Results: The results showed that the factors associated with heat strain in tofu making industry workers were heat stress ( P = 0.001), age ( P = 0.003), gender ( P = 0.007), and obesity ( P = 0.012). Conclusions : Work environment heat stress, age, gender, and obesity are factors associated with heat strain in tofu making industry workers. Efforts to control heat strain need to be made, especially through improving the work climate and weight loss programs for obese workers.